Genome-Wide Characterization of HSP90 Gene Family in Cucumber and Their Potential Roles in Response to Abiotic and Biotic Stresses - Zhang, Kaijing; He, Shuaishuai; Sui, Yihu; Gao, Qinghai; Jia, Shuangshuang; Lu, Xiaomin; Jia, Li (Frontiers in Genetics, 2021)
Heat shock protein 90 (HSP90) possesses critical functions in plant developmental control and defense reaction. HSP90 gene family has been studied in various plant species. However, the HSP90 gene family from cucumber has not been characterized in detail. In this study, a total of 6 HSP90 genes were identified from cucumber genome, which distributed to five chromosomes. Phylogenetic analysis divided the cucumber HSP90 genes into two groups. The structural characteristics of cucumber HSP90 members in the same group were similar but varied among different groups. Synteny analysis showed that only one cucumber HSP90 gene, Csa1G569290, was conservative, which was not collinear with any HSP90 gene in Arabidopsis and rice. The other 5 cucumber HSP90 genes were collinear with 5 Arabidopsis HSP90 genes and 6 rice HSP90 genes. Only one pair of paralogous genes in the cucumber HSP90 gene family, namely one pair of tandem duplication genes (Csa1G569270/Csa1G569290), was detected. The promoter analysis showed that the promoters of cucumber HSP90 genes contained hormone, stress and development-related cis-elements. With the big data of cucumber transcriptome sequencing, tissue-specific expression analysis revealed that only one cucumber HSP90 gene Csa3G183950 was highly expressed in tendril but low or not expressed in other tissues, while the other 5 HSP90 genes were expressed and even highly expressed in all tissues. Furthermore, the expression levels of cucumber HSP90 genes were differentially induced by temperature and photoperiod, gibberellin (GA), downy mildew and powdery mildew stimuli. Two cucumber HSP90 genes, Csa1G569270 and Csa1G569290, were all differentially expressed in response to abiotic and biotic stresses, which means these two HSP90 genes play important roles in the process of cucumber growth and development. These findings improve our understanding of cucumber HSP90 family genes and provide preliminary information for further studies of cucumber HSP90 genes functions in plant growth and development.